2005
DOI: 10.1038/nn1439
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ acts at the C terminus of SNAP-25 to mediate presynaptic inhibition

Abstract: Presynaptic inhibition mediated by G protein-coupled receptors may involve a direct interaction between G proteins and the vesicle fusion machinery. The molecular target of this pathway is unknown. We demonstrate that Gbetagamma-mediated presynaptic inhibition in lamprey central synapses occurs downstream from voltage-gated Ca(2+) channels. Using presynaptic microinjections of botulinum toxins (BoNTs) during paired recordings, we find that cleavage of synaptobrevin in unprimed vesicles leads to an eventual exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
203
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(221 citation statements)
references
References 49 publications
16
203
0
1
Order By: Relevance
“…Because of the rapidity of release (a few milliseconds), it is unlikely that second messengers are involved in control of the tonic block. Rapid control could potentially be achieved (i) by GPCRs targeting Ca 2ϩ channels (31,34,41), (ii) by GPCRs targeting the release machinery via G ␤ ␥ (11,12,42), or (iii) by a rapid voltagedependent shift of the GPCR affinity and a direct interaction of the GPCR itself with the release machinery (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the rapidity of release (a few milliseconds), it is unlikely that second messengers are involved in control of the tonic block. Rapid control could potentially be achieved (i) by GPCRs targeting Ca 2ϩ channels (31,34,41), (ii) by GPCRs targeting the release machinery via G ␤ ␥ (11,12,42), or (iii) by a rapid voltagedependent shift of the GPCR affinity and a direct interaction of the GPCR itself with the release machinery (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…By targeting SNAP-25, BoNT/A may prevent the SNAREmediated translocation of receptors to plasma membrane, such as N-methy-D-aspartate receptor and transient receptor potential vanilloid 1 (TRPV1) MorenillaPalao et al, 2004;Shimizu et al, 2012). In addition, it may prevent the G protein interaction with SNARE-dependent exocytotic machinery (Gerachshenko et al, 2005).…”
Section: Additional Actions Of Bont/a Mediated By Snap-25mentioning
confidence: 99%
“…Gβγ can have many immediate effectors, including PLCβ, ACs, ion channels, kinases and components of the synaptic vesicle release machinery Cabrera-Vera et al, 2003;Stehno-Bittel et al, 1995;Sullivan, 2005;Gerachshenko et al, 2005). It has been previously demonstrated that D 2 receptors can regulate ACII activity via Gβγ mediated activation of PLCβ (Tsu and Wong, 1996).…”
Section: Blocking the Gβγ Cascade Reveals A Da-induced Gα I/o Mediatmentioning
confidence: 99%